Correlation of reactivity and properties of wood chars - Kumar M.; Gupta R.C. (My University, 2025)
Correlations between the reactivity and electrical, structural and physical properties of acacia and eucalyptus wood chars were determined. As these properties require much less time to measure than the reactivity does, they can be considered as an alternative to reactivity testing currently used for quality control. © 1994.